Partisipasi Politik Masyarakat Dalam Diskursus Kolom Kosong Pada Pemilihan Bupati di Kabupaten Enrekang - Khaerah, Nur; Junaedi, Junaedi; Muslimin, Muslimin (Universitas Gorontalo, 2019)
This article discusses Community Political Participation in the selection of regent and deputy regent candidates in the Enrekang Regency and to find out the efforts of the Empty column winning team in increasing the political articipation of the community to choose the empty column. The research method used is a qualitative descriptive method and using two kinds of data, namely primary data and secondary data. The results of this study indicate that the form of community political participation in the selection of the district Head and Deputy Regent of Enrekang district is the Electoral Activity, Lobbying, Organizational Activity, Contacting and Violence. Community participation in the electoral system and of course their have own reasons, star because of the political awareness of the community and most of them assume that choosing is the right of each individual so that everyone is free to choose according to their wishes without being influenced by others. The effort of the empty column winning team in increasing community participation to select the blank box is to focus on certain issues such as socializing the failure of the detention regentArtikel ini membahas tentang Partisipasi politik masyarakat dalam pemilihan calon Bupati dan Wakil Bupati di Kabupaten Enrekang dan untuk mengetahui upaya tim pemenangan Kolom Kosong dalam meningkatkan Partisipasi politik masyarakat untuk memilih Kolom Kosong. Adapun metode penelitian yang digunakan adalah metode deskriptif kualitatif dengan menggunakan dua macam data, yaitu data primer dan data sekunder. Hasil penelitian ini menunjukkan bahwa bentuk partisipasi politik masyarakat dalam pemilihan Bupati dan Wakil Bupati Kabupaten Enrekang yaitu dengan Electoral Activity, Lobbying, Organizational Activity, Contacting dan Violence. Keikutsertaan masyarakat dalam sistem pemilu dan tentunya memiliki alasan masing-masing, mulai karena kesadaran politik masyarakat. Upaya Tim Pemenangan Kolom Kosong dalam Meningkatkan Partisipasi Politik Masyarakat untuk Memilih Kolom Kosong adalah dengan memfokuskan pada isu tertentu seperti mensosialisasikan kegagalan dari bupati petahana